Citrus aurantifolia-derived carbon quantum dots with red fluorescence emission for codelivery with curcumin as theranostic liposomes for lung cancer - Angshuman Sonowal; Alakesh Bharali; Trideep Saikia; Susankar Kushari; Madhuchandra Lahon; Jun Moni Kalita; Nikhil Biswas; Damiki Laloo; Bhanu P. Sahu (SpringerOpen, 2024)
Abstract Background Carbon dots (CDs) derived from Citrus aurantifolia represent a promising platform for advanced cancer therapy and diagnostics (theranostics). These CDs are synthesized through a sustainable and cost-effective hydrothermal method, utilizing fruit juice as a green carbon source. Despite the potential, research on the synthesis of citrus-based CDs, especially regarding their red fluorescence emission, which is crucial for enhanced tissue penetration and biomedical efficacy, remains limited. Results In this study, CDs were successfully synthesized from C. aurantifolia fruit, yielding nanoparticles below 5 nm in size (PDI 0.231 ± 0.04). Characterization revealed favorable optical properties, including excitation-dependent fluorescent behavior with prominent red emission under higher excitation wavelengths, a quantum yield of 8.17%, and stable photoluminescence. Chemical composition analysis using XPS, FTIR, and XRD confirmed the purity and structure of the CDs. To explore their biomedical application, CDs were co-loaded with curcumin into liposomes. The formulations had a mean size of 177.2 ± 3.6 nm (PDI 0.270 ± 0.012), demonstrated efficient drug entrapment (60.32 ± 2.24%), and exhibited rapid release kinetics, with 90.21 ± 2.16% of the drug release within 8 h. In vitro studies using A549 lung cancer cells demonstrated superior cellular uptake and cytotoxicity of Cur-CD-loaded liposomes compared to curcumin alone (Cur-Suspension), achieving IC50 values of 0.093 ± 0.011 µg/ml and 0.016 ± 0.006 µg/ml, respectively. Conclusion This research underscores C. aurantifolia as a viable natural source for green CD synthesis. The obtained CDs with red fluorescence emission, optimized through reaction conditions and excitation wavelengths, hold promise for enhanced biological applications, particularly in the realm of lung cancer therapy. The findings advocate for further exploration and refinement of citrus-based CDs as versatile theranostic agents, capitalizing on their sustainable origins and potent biomedical properties. The combination of citrus-derived CDs with curcumin loaded into liposomal formulations represents a potent theranostic strategy for lung cancer treatment, leveraging the unique properties of CDs and their potential for targeted and effective therapy. Graphical abstract